Efektivitas Manajemen Risiko pada Perbankan Syariah dalam Menghadapi Ketidakpastian Ekonomi Global - muqaffa, dzaki (Maliki Interdisciplinary Journal, 2025)
Islamic banking faces various risks due to global economic uncertainty, such as price fluctuations and changes in monetary policy. Risk management is essential to maintain operational stability while adhering to Sharia principles, which prohibit riba (usury), gharar (uncertainty), and maisir (gambling). This study identifies key risks such as credit, liquidity, market, operational, and Sharia compliance risks, and examines strategies for managing them. The findings show that effective risk management can protect assets and increase customer trust. Enhancing literacy, training, and developing innovative Sharia-compliant instruments are crucial for addressing future challenges. Islamic banks need to improve human resource (HR) literacy and training related to risk management, particularly in understanding Islamic products and risk mitigation strategies amid global economic uncertainty. Furthermore, it is crucial for Islamic banks to develop more innovative Islamic financial instruments, such as sukuk and Islamic hedging, to more effectively manage exchange rate and liquidity risks.